ANOTHER SIDE OF ISLAM IN BANTEN: The Socio-Political Roles of Jawara during the New Order Era 1966-1998 (JOURNAL OF INDONESIAN ISLAM, 2013)
This paper deals with the socio-political roles of jawara in Banten as both traditional and modern leaders during the New Order period 1966-1998. This paper shows that Banten is not only an area of piety, but also an area of tradition and violence in different forms. In the colonial period, jawara mounted resistance—along with ulama—aimed at overthrowing not only existing political regimes but also the socio-cultural order as it then existed. During the New Order, this development was altered with the cooptation of both ulama and jawara by Golkar. By envolving to the state and adjusting to the new atmosphere of the political situation, jawara and ulama created new positions where they gradually expanded their power, status and wealth. Throughout the Suharto’s power, they demonstrated the patron-client relationships with the government.